2016
DOI: 10.1007/s11926-016-0623-7
|View full text |Cite
|
Sign up to set email alerts
|

Direct Oral Anticoagulants Use in Antiphospholipid Syndrome: Are These Drugs an Effective and Safe Alternative to Warfarin? A Systematic Review of the Literature

Abstract: The recent RAPS trial demonstrated that APS patients treated with rivaroxaban had a significant twofold-increased thrombin potential, suggesting a higher thrombotic risk, in comparison with warfarin users. Furthermore, several reports of APS patients treated with DOACs have raised safety issues. Our systematic review identified 122 published APS patients treated with DOACs; among them, 19 experienced a recurrent thrombosis while on DOACs. Of note, triple positivity (positivity of all three laboratory criteria … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(50 citation statements)
references
References 47 publications
1
48
0
1
Order By: Relevance
“…Similarly, there are at least 28 other cases of failure of NOACs in preventing thrombotic events in APS reported in literature thus far, which have been summarized in Table 1. Dufrost et al 13 recently published a systematic literature review of 122 APS patients identified in the literature to have been treated with NOACs and found that 19 of them had recurrent thrombosis while on NOACs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, there are at least 28 other cases of failure of NOACs in preventing thrombotic events in APS reported in literature thus far, which have been summarized in Table 1. Dufrost et al 13 recently published a systematic literature review of 122 APS patients identified in the literature to have been treated with NOACs and found that 19 of them had recurrent thrombosis while on NOACs.…”
Section: Discussionmentioning
confidence: 99%
“…The RAPS study did not have sufficient numbers of patients in either arm to achieve enough power for definite clarification. 13 The investigators reported non-inferiority of rivaroxaban as compared to VKAs, as the ETP for rivaroxaban did not reach the non-inferiority level, which was set at < 20% difference from warfarin in mean percentage change. However, the peak thrombin generation for rivaroxaban was significantly higher at 93.8 nMol/L as compared to warfarin at 79.9 nMol/L.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most recent American Heart Association/American Stroke Association (AHA/ASA) guidelines recommend antiplatelet therapy for cases with ischemic stroke or TIA and positive aPL that do not fulfill the criteria for APS, and an option for anticoagulation when criteria for APS are met . The off‐label use of direct oral anticoagulants (DOACs) is controversial . The only randomized phase III trial comparing rivaroxaban with warfarin in high‐risk APS patients with triple antibody positivity was terminated prematurely due to increased cerebrovascular events in the rivaroxaban group .…”
Section: Causes Of Recurrent Multi‐territory Embolic Cerebral Infarctionmentioning
confidence: 99%
“…Bleeding events and overall adverse events were also similar between the groups [14]**. While a full recounting of this important trial is beyond the scope of this brief review, we would refer you to a detailed comment on the topic [66]. Related to our discussion of the complement pathway, a post-hoc analysis of the RAPS trial revealed that, prior to randomization, APS patients had significantly higher markers of complement activation as compared with normal controls [19]*.…”
Section: Complement: At the Intersection Of Coagulation And Inflammatmentioning
confidence: 99%